Potential of Cytokines in the Management of Intervertebral Disc Degeneration - Yu, Huiyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The illness known as intervertebral disc degeneration (IDD) is characterized by discomfort in the intervertebral discs. The IDD is made up of the annulus fibrosus (AF) and nucleus pulposus (NP), which function as a joint and cushion for the spine. IDD can develop with ageing, which can cause the NP to herniate and cause pain. IDD patients experience detrimental effects on their quality of life and mental health in addition to their physical health. It also poses a critical economic burden on society as a whole. Imaging techniques used for the diagnosis are disc herniation, X-ray plain film, CT, and MRI are discussed as imaging modalities, with MRI being particularly useful for diagnosing disc herniation. Treatment approaches range from conservative methods to surgical intervention, related to the type of IDD. Nonsteroidal anti-inflammatory medications, rest, traction therapy, and physical therapy are examples of non-surgical therapies. Options for surgery include conventional open surgery, microsurgical lumbar discectomy, minimally invasive IVD removal surgery, and artificial IVD replacement surgery. Many studies are focused on the role of cytokines to explain the cause of IDD. And these cytokines can be classified as cell cycle inhibitor, proinflammatory factor and growth factor. The article highlights cell cycle inhibitors (p16INK4a and p53), proinflammatory factors (IL-1β and TNF-α), and growth factor (TGF-β) involvement in IDD. However, currently, there are no cytokine-based treatments available for IDD in clinical practice. Future research could focus on developing new treatment or prevention targets for IL-1β or TNF-α.